2008
DOI: 10.1371/journal.pone.0002851
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Musculoskeletal Impairment in Rwanda: Prevalence, Causes and Service Implications

Abstract: BackgroundAccurate information on the prevalence and causes of musculoskeletal impairment (MSI) is lacking in low income countries. We present a new survey methodology that is based on sound epidemiological principles and is linked to the World Health Organisation's International Classification of Functioning.MethodsClusters were selected with probability proportionate to size. Households were selected within clusters through compact segment sampling. 105 clusters of 80 people (all ages) were included. All par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 5 publications
5
53
2
Order By: Relevance
“…3 A recent survey of the orthopaedic needs of children in Rwanda suggested that 3% were suffering from a musculoskeletal impairment due to infection. 4,5 Nearly two billion children under the age of 18 live in developing countries, and 400 million in the least-developed countries, compared to only 200 million in industrialised countries. 6 If the prevalence of musculoskeletal impairment due to infection across the leastdeveloped countries is similar to that in Rwanda, in these countries alone approximately 12 million children are affected.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…3 A recent survey of the orthopaedic needs of children in Rwanda suggested that 3% were suffering from a musculoskeletal impairment due to infection. 4,5 Nearly two billion children under the age of 18 live in developing countries, and 400 million in the least-developed countries, compared to only 200 million in industrialised countries. 6 If the prevalence of musculoskeletal impairment due to infection across the leastdeveloped countries is similar to that in Rwanda, in these countries alone approximately 12 million children are affected.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The demand in Sierra Leone for musculoskeletal care appears to be great when compared with estimates from previously published population-based and extrapolative studies [2,27,30]; however we are aware of only one other population-based survey of musculoskeletal problems in a developing country [2]. Atijosan et al [2] measured musculoskeletal impairment in Rwanda as 5.2% overall prevalence using a standardized survey, history, and physical examination by a trained physiotherapist.…”
Section: Discussionmentioning
confidence: 94%
“…By separating traumatic musculoskeletal problems from nontraumatic, better insight into the health needs of a population can be achieved. A previous study of musculoskeletal disease in low-and middle-income countries focused on disability attributable to musculoskeletal problems [2], which may capture short-term problems such as injury. The capacity to deal with disabling, chronic, and acute musculoskeletal conditions will be met only by increasing surgical capacity in low-and middleincome countries [6,19,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations